Beyond Collaboration: The Impact of Partner Knowledge, Relational Skills, and Internal Communication on SME’s Performance - Setiarini, Mersiana (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2025)
This study aims to analyze the influence of network capabilities consisting of Partner Knowledge, Relational Skills, and Internal Communication on SME’s performance. Partner Knowledge plays a role in forming information exchange routines that support business processes, while Relational Skill refers to the organization's ability to build strong relationships to obtain reliable market information. Meanwhile, Internal Communication functions as a routine interaction mechanism that improves collaborative competence and accelerates organizational performance. This study uses a quantitative approach with a survey method involving SME actors as respondents. The data collected were analyzed using regression analysis techniques to test the relationship between the variables studied. The results of the study indicate that the three network capabilities contribute significantly to improving SME’s performance, both individually and simultaneously. This finding confirms that effective network capability management can improve competitiveness, operational efficiency, and innovation in SME Performance.